SEJARAH DAN PERKEMBANGAN PENDIDIKAN ISLAM DI KOTA JAMBI - Siti Heidi Karmela (Universitas Batanghari Jambi, 2017)
Abstract: Education is an attempt to develop ability, to establish personality, and to build dignified civilization in order to educate the certain nation. Furthermore, education is a media that is supposed to educate generations. Education is presented to build whole personality, cultured and civilized, whether through formal or informal education. Education as a system is human work in a form of component which has a functional relationship in developing transformational process or changes in person’s behavior in order to gain particular quality. Education is also a preventive alternative in building better generation. In orde to achieve these education goals, education institution is needed as an organizer of formal, informal, and non formal education. Those three organization has been a part of Indonesian history in education system. Like what Ki Hajar Dewantara stated that education in Indonesian has been occurred in Indonesia before colonization era until national movement in a form of course in written and oral general knowledge, discussion group, politics course, and public school that has been into a program that appears in whole modern organization in that era.Keyword : Education, Formal Education, Informal Education and Non-Formal Education